MEMBANGUN GENERASI BERKARAKTER: PEMBINAAN NILAI-NILAI POSITIF DALAM MENCEGAH PENYALAHGUNAAN NARKOBA DI GAMPOENG PADANG SAKTI KECAMATAN MUARA SATU KOTA LHOKSEUMAWE - Sukmawati, Cut; Nazaruddin, M.; Subhani, Subhani; Ameliany, Nanda; Yunanda, Rizki; Murniati, Murniati; Aditya, Wanda; Auliana, Cut (Universitas Malikussaleh, 2023)
The main problem that occurs in this service is the anxiety found around drug abuse which has touched the very foundation of life in society. The method of implementing service is carried out in the stages of preparation, coaching and counseling as well as monitoring and evaluating activities. The results obtained from this service activity are that it can foster positive values in providing constructive/constructive contributions in terms of preventing drug abuse. To measure the influence on partners (in this case the Padang Sakti Gampoeng community), several methods are applied by the service team, namely: measuring initial knowledge and attitudes, testing knowledge after the seminar, evaluating changes in attitudes and participant feedback. Measuring the influence and impact on Malikussaleh University in carrying out its service, the service team uses several indicators and evaluation methods as follows: developing networks and relationships, increasing reputation, publication and dissemination of results. Finally, to measure the influence and impact on the service team in carrying out service, the team uses several indicators and evaluation methods as follows: participation and attendance, participant satisfaction, impact of participant knowledge and attitudes, collaboration with partners, increased knowledge of the service team, increased cooperation between the service team and partners (Gampoeng Padang Sakti device), and increased reputation.